Training effects of the FIFA 11+ and Harmoknee on several neuromuscular parameters of physical performance measures - Ayala, F.; Pomares-Noguera, C.; Robles-Palazo, F. J.; del Pilar Garcia-Vaquero, M.; Ruiz-Peez, I.; Hernandez-Sanchez, S.; De Ste Croix, M. (International Journal of Sports Medicine, 2017)
The main purpose of this study was to analyse the training effects of the FIFA 11+ and Harmoknee on several parameters of physical performance measures in youth amateur football players. 41 adolescent players were randomised within each team into 2 groups (team 1: control vs. FIFA 11+; team 2: control vs. Harmoknee). The FIFA 11+ and Harmoknee groups performed the program 3 times a week for 4 weeks; the control groups completed their usual warm-up routines. 13 physical performance measures (joint range of motion, dynamic postural control, single legged hop limb symmetry, sprint time, jumping height and agility) were assessed. All physical performance parameters were compared via a magnitude-based inference analysis. Significant between-group differences (in favour of the FIFA 11+ players) were found for dynamic postural control (anterior [2.5%] and posteromedial [7.2%] distances), single legged hop limb symmetry (side-to-side symmetry during a triple hop test [8.3%]), 10 (8.4%) and 20 (1.8%) m sprint times and jumping height (9.1%) neuromuscular outcomes. For the Harmoknee, significant differences (in comparison to its paired control group) were found only for 10 (2.7%) and 20 (2.9%) m sprint times and jumping height (9.7%). Therefore, the main findings of this study suggest exchanging traditional warm-up programmes for the FIFA 11+ in male youth soccer players based on its superior effects on some neuromuscular parameters (sprinting, jumping and stability) of physical performance.